The ‘woody clade’ in Kalanchoe: reinstatement and amendment of K. subg. Calophygia (Crassulaceae subfam. Kalanchooideae) published by Bernard Marie Descoings in 2006 - Smith, Gideon F. (Phytotaxa, 2023)
Up to now, four subgenera were widely upheld in Kalanchoe (Crassulaceae subfam. Kalanchooideae): (1) the autonymic K. subg. Kalanchoe, (2) K. subg. Alatae, (3) K. subg. Bryophyllum, and (4) K. subg. Kitchingia. To accommodate what is often referred to as the ‘woody clade’ group of species at the rank of subgenus in Kalanchoe, this cluster is here recognised as the fifth subgenus, K. subg. Calophygia Desc. emend. Gideon F.Sm. Kalanchoe subg. Calophygia, as published by Bernard Marie Descoings in 2006, is therefore reinstated, but with taxonomic amendments to the circumscription of the subgenus to retain only the so-called ‘woody clade’ species. These species are generally low-growing and pseudo-rosulate to multi-branched, shrubby or arborescent perennials of which, with a few notable exceptions, virtually all external surfaces are variously covered by a tomentum consisting of glandular or stellate hairs or minute scales.